Validation of the COBRA nomogram for the prediction of cancer specific survival in patients treated with radical cystectomy for bladder cancer: An international wide cohort study. Issue 10 (October 2021) - De Nunzio, Cosimo; Franco, Antonio; Simone, Giuseppe; Tuderti, Gabriele; Anceschi, Umberto; Brassetti, Aldo; Daneshmand, Siamak; Miranda, Gus; Desai, Mihir M.; Gill, Inderbir; Abol-Enein, Hassan; Molinaro, Emilio; et al.
Abstract: Background: Recently, the Cancer of the Bladder Risk Assessment (COBRA) score has been introduced to estimate cancer specific survival (CSS) after radical cystectomy for bladder cancer. Objectives: Aim of our study was to validate the COBRA score, assessing the effect of age, tumor stage and lymph-nodes status on CSS after cystectomy in patients with bladder cancer. Design, setting, and participants: A consecutive series of 2395 patients with primitive or recurrent bladder cancer treated with radical cystectomy in 4 centers were evaluated. Outcome measurements and statistical analysis: The role of COBRA score as predictor of CSS was assessed using the Kaplan Meier and Cox proportional hazards analyses. Accuracy of COBRA score was evaluated by Harrell's C test. Results and limitations: Median age was 66 (IQR 58/73) years. Overall, at a median follow-up of 48 (IQR 22/92) months, 642 patients (27%) died of bladder cancer. On Cox proportional hazards analyses, COBRA score was a significant predictor of CSS (HR 1.54, 95%CI 1.47–1.61) (Table 1). The predictive accuracy of the COBRA score was 0.71. A sub analysis including pooled COBRA score (0 vs 1–3 vs 4 vs 5–7) improved the clinical applicability with the same accuracy. Conclusion: In our experience, the COBRA score is an excellent tool to predict cancer specific survival. The COBRA Score represents a practical and easy tool that may help urologists to classify the CSS of patients treated with radical cystectomy, to predict the oncological outcome and finally to counsel bladder cancer patients.